2006
DOI: 10.1188/06.onf.s1.5-12
|View full text |Cite
|
Sign up to set email alerts
|

Advances in How Clinical Nurses Can Evaluate and Improve Quality of Life for Individuals With Cancer

Abstract: Clinical nurses can involve individuals with cancer in rating their QOL to assist in providing high-quality care that is directed at positively affecting QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 54 publications
1
35
0
4
Order By: Relevance
“…6Y8 Studies have shown that the diagnosis and treatment of cancer affect QOL 6Y9 and oncology nurses often perceive patients' QOL worse than the patients themselves do. 6 Therefore, QOL has become an important focus of both oncology nursing practice and research. Quality of life has often been identified as a top research priority by the Oncology Nursing Society, 10,11 and other oncology nursing organizations have focused their attention on QOL of cancer patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6Y8 Studies have shown that the diagnosis and treatment of cancer affect QOL 6Y9 and oncology nurses often perceive patients' QOL worse than the patients themselves do. 6 Therefore, QOL has become an important focus of both oncology nursing practice and research. Quality of life has often been identified as a top research priority by the Oncology Nursing Society, 10,11 and other oncology nursing organizations have focused their attention on QOL of cancer patients.…”
mentioning
confidence: 99%
“…12 Quality of life is an outcome indicator that is sensitive to nursing interventions, and oncology nurses are in a key position to influence patients' QOL. 6 The purpose of this study was to describe over time the QOL of Icelandic cancer patients initiating a new chemotherapy protocol for either newly diagnosed or progressive disease. In addition, this study assessed the relationship between demographic factors, disease parameters, symptoms of anxiety and depression, and QOL.…”
mentioning
confidence: 99%
“…These observations are consistent with the meeting of patients' needs and the support that they received from the ICCN program. Patient-centered communication, a core value in the ICCN model, is considered an important mechanism by which nurses can affect quality of life because care is individualized and focused on selection of interventions relevant to identified needs (King, 2006).…”
Section: Impact Of Specialized Oncologymentioning
confidence: 99%
“…Similar to the SEIQOL, the Patient-Generated Index allows individuals to select the five most important areas for their QOL, rate how badly each area has been affected and prioritize the areas as to which they would most like to improve (King, 2006).…”
Section: Measuring Quality Of Lifementioning
confidence: 99%
“…Two instruments designed to overcome the problem of imposing an external value system on individuals rather than allowing them to describe their QOL in terms of factors they consider important are the Subjective Evaluation ofIndividual QOL (SEIQOL) and the Patient-Centered Index (King, 2006).…”
Section: Measuring Quality Of Lifementioning
confidence: 99%